Public Health Behavior Change Communication Strategies in Accelerating the Reduction of Stunting in North Minahasa Regency - Reiner Richard Onsu; Grace Jane Waleleng; Joula J. Rogahang (Journal La Sociale, 2023)
Communication Strategy for Community Health Behavior Change in Accelerating Stunting Reduction in North Minahasa Regency, through aspects (1) Announcing: socialization and counseling to pregnant women and parents who have children under 5 years old through lectures, presentations and questions and answers. (2) Motivating: Pay attention to nutritional intake, Conduct regular health checks for pregnant women and toddlers, Overcome the problem of children having difficulty eating by providing variants in food, Maintain environmental sanitation, provide education to pregnant and lactating women in the "Hope of the Lover of the Heart" program, Carry out complete vaccination of babies born as recommended. (3) Educating: Education on proper and nutritious eating patterns with the "Fill the Plate" program in a Canteen. Parenting education Education risks the threat of infectious diseases if not using sanitation and clean water. (4) Information Dissemination (Informing): Directly by means of socialization with verbal communication, also using paflet media, posters and videos. (5) Supporting decision making: Supported by the PPKB Office, Health Office, Social Service, PMD, Food Office, Disdukcapil, Private Sector, TP-PKK, TNI. Communication Strategy for Public Health Behavior Change in Accelerating Stunting Reduction contributes to increasing public knowledge and sustainable social strengthening through efforts to accelerate stunting reduction.